Improving gel formation of rice starch added with cross‐linked resistant starch prepared from rice starch. Issue 9 (22nd June 2015) - Yu, Mengying; Shin, Malshick
Abstract : The gel formation properties of non‐waxy rice starch with cross‐linked resistant starch with phosphate (RS4, 10, 20, and 30% based on rice starch) prepared from three rice varieties with different amylose (AM) content were investigated to increase dietary fiber content, improve gel structure, and reduce the glycemic index of rice products. The AM contents of rice starches were 1.71% in Hanganchal1, 22.47% in Nampyeong, and 33.39% in Goamy. All RS4 showed A‐type crystallinity and their RS levels were 46.91, 54.54, and 66.01%, respectively. The initial pasting temperatures of RS4 added rice starches increased as RS4 contents increased, but peak and breakdown viscosities and enthalpy change (△H) reduced. The RS4 addition improved gel shape and texture properties including hardness, cohesiveness, and gumminess, except the 30% Goamy RS4 added gel. The 20% RS4 addition was appropriate to form rice starch gels. The network structure of RS4 added gel formed more regular and firmer than that of control, because RS4 granules were entrapped within the gel matrix like observed by light microscope and scanning electron microscopy. It is suggested that RS4 not only assist in forming a rigid network structure but also increasing a dietary fiber content.